Fertiliser use Behaviour of Rice Farmers of Kerala - Geethakutty P S (Department of Agricultural Extension, College of Horticulture, 1993)
The study was conducted with the main objective of developing an index for measuring the fertilizer use behaviour of rice farmers. A total of 300 rice farmers were selected following multistage random sampling procedure, 60 from each District, so selected that each District represented one NARP Zone. Besides farmer respondents, 40 agricultural scientists, 40 agricultural extension personnel and 40 input dealers were also selected as other categories of respondents for the study. The Composite Fertiliser Use Behaviour Index (CFUBI) was developed by identifying six dimensions of fertilizer/ manure use for rice, (quantity, time of application, split application, type, method of application and related management practices). The weightages of the identified six dimensions were obtained through judges’ rating and also through the relevancy rating of the practices under the identified dimensions. The CFUBI derived by the formula method was compared with the index developed by the Principal Component Analysis (PCA) method. Based on relevancy rating and pilot study, 17 behavioural characteristics were selected as independent variables. The variables were quantified using standardized procedures. Mean and percentage analysis, Delinious Hodges Cumulative Root ‘f’ stratification, Critical difference, Coefficient of variation analysis of variance, kendall’s coefficient of concordance, Chi – square analysis, Correlation analysis, Multiple regression analysis and Principal Component Analysis were the statistical tools used for data analysis. The study revealed that more than 60 per cent of rice farmers were under ‘good’ and ‘satisfactory’ categories based on their CFUBI. The NARP Central Zone had highest percentage of farmers under ‘good’ category of CFUBI, while the Problem Zone had the highest percentage of farmers with regard to the use of nitrogenous, phosphatic and potassic fertilizers. The High Range Zone had the highest percentage of farmers with respect to the use of organic manures. Based on the use of nitrogenous and phsphatic fertilizers, majority of the farmers were categorized under either ‘good’ or ‘satisfactory’ category, while with respect to the use of potassic fertilisers, it was found that farmers were almost similarly distributed under ‘good’, ‘satisfactory’, ‘poor’ and very poor’ categories. The Problem zone and Northern zone were found to be ‘very poor’ with respect to the use behaviour of organic manures and potassic fertilisers respectively. There was significant difference among the five NARP Zones in respect of the different dimensions of use of nitrogenous, phosphatic and potassic fertilizers and organic manures. The use behaviour of potassic fertilisers had the highest factor loadings in explaining variability in the CFUBI of farmers followed by the use behaviour of nitrogenous fertilisers. Split application of nitrogenous fertilisers, quantity and time of application of phosphatic fertilisers, quantity and split application of potassic fertilisers and quantity of organic manures were found significant in predicting the AYI of farmers. The behavioural characteristics of farmers found to be significant in predicting the fertiliser use behaviour of rice farmers were main occupation, level of aspiration, rational decision making ability, attitude towards fertiliser use, information source utilisation and economic performance index. The important technological and situational factors contributing to fertiliser use hehaviour as perceived by the farmers, extension personnel, scientists and input dealers were irrigation facilities, perceived appearance of crop stand, drainage facilities, price of produce, availability of rain and availability of labour. Lack of knowledge about fertiliser use, lack of assured irrigation facilities, high cost of fertilizers, high rate of labour wages, increased incidence of pests and diseases, non availability of organic manures and improper drainage facilities were the major constraints in the composite fertilizer use behaviour of rice farmers in Kerala.